Regulatory oversight, corporate governance and audit fees. - Goh, Soo Ying. (2008)
This paper examines the moderating effect of regulatory oversight on the relationship between corporate governance characteristics and audit fees. The result is consistent with the premise that regulatory oversight provides close monitoring which partially substitutes and thus diminishes the role of audit as a corporate control mechanism.